Digital Claim Readiness as a Mediating Factor Between Marine Cargo Insurance Coverage and Compensation Recovery in Indonesian Maritime Logistics - Veronika Saragih (Jurnal Penelitian Samudra, 2026)
The increasing complexity of global maritime logistics has intensified the importance of marine cargo insurance in mitigating financial losses arising from cargo damage, loss, and transportation delays. Despite the widespread adoption of marine cargo insurance, many cargo owners continue to experience difficulties in obtaining full compensation due to incomplete documentation, delayed claim submission, and limited digital integration among shipping stakeholders. Existing studies have primarily focused on legal liability and insurance coverage while paying limited attention to the operational readiness required to ensure successful compensation recovery. This study investigates the relationship between marine cargo insurance coverage and compensation recovery by introducing Digital Claim Readiness (DCR) as a mediating construct. Digital Claim Readiness refers to an organization's capability to prepare, verify, and submit insurance claims through integrated digital documentation, electronic cargo tracking, and real-time logistics information systems. A quantitative research design was employed using Structural Equation Modeling (SEM-PLS). Data were collected from freight forwarders, shipping companies, cargo owners, marine surveyors, and insurance companies operating in major Indonesian ports. The proposed conceptual model evaluates the influence of insurance coverage quality, digital documentation systems, claim readiness, and insurer responsiveness on compensation recovery performance. The study proposes that Digital Claim Readiness significantly mediates the relationship between insurance protection and compensation effectiveness. Organizations implementing integrated digital claim management systems are expected to achieve faster claim settlement, lower dispute rates, and higher compensation recovery ratios than organizations relying on conventional documentation procedures. This research contributes to maritime insurance literature by introducing Digital Claim Readiness as a novel operational capability within marine cargo insurance management. The findings are expected to support the development of digital insurance ecosystems that improve transparency, operational efficiency, and risk management across maritime logistics.